Leading the way to heaven - Rhijn, Carine van, author.
1 online resource.
Keywords: "Starting from manuscripts compiled for local priests in the Carolingian period, this book investigates the way in which pastoral care took shape at the local levels of society. They show what illiterate lay people learned about their religion, but also what priests themselves knew. This volume is of great use to upper-level undergraduates, postgraduates and scholars interested in the ecclesiastical history of Europe in the Carolingian period"--